ANTIFUNGAL EFFECTS OF ALOE VERA IRRIGANT ON CANDIDA ALBICANS BIOFILM - ASTINAH; NAZAR, KAMIZAR; MEIDYAWATI, RATNA (International Journal of Applied Pharmaceutics, 2019)
Objective: Candida albicans tolerates unfavorable environmental conditions by forming biofilms, which can cause problems following endodontic treatments. C. albicans is the most common fungus found in failed root canals. Using natural irrigants with good antifungal properties for use as synthetic irrigant alternatives during root canal cleaning and shaping is very important. This study aimed to analyze the effects of Aloe vera on C. albicans biofilm. Methods: C. albicans biofilm was divided into the following five groups: Group I, no treatment (control group); Groups II, III, and IV, A. vera with a concentration of 100%, 75%, and 50%, respectively; and Group V, Ethylenediaminetetraacetic acid (EDTA) 17%. Results: The average biofilm colony count for C. albicans for the A. vera 100%, 75%, and 50% groups was higher than that for the EDTA 17% group but lower than that for the control group. Conclusion: A. vera has antifungal effects on C. albicans biofilm, with the greatest effect occurring at 75% concentration.